2006
DOI: 10.1063/1.2374809
|View full text |Cite
|
Sign up to set email alerts
|

Microlens array fabrication by laser interference lithography for super-resolution surface nanopatterning

Abstract: A technique for large area and fast speed surface nanopatterning of photopolymer surface with laser irradiation through microlens array (MLA) was demonstrated. The laser beam was split into many focused tiny light spots by a 1μm diameter MLA fabricated by laser interference lithography followed by reflow and reactive ion etching. The fabricated MLA exhibits excellent uniformity and surface quality. Up to 6 250 000 nanopatterns can be fabricated over an area of 5×5mm2 under KrF excimer laser single pulse exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…Although its wavelength is in the near IR range, it is one of the very promising tools to fabricate nanostructures due to the multi-photon absorption effect. The results of this work show that the optical diffraction limit can be overcome by using a MLA with small lens diameter in combination with appropriate choice of laser power Lim et al 2006). …”
Section: Introductionmentioning
confidence: 86%
“…Although its wavelength is in the near IR range, it is one of the very promising tools to fabricate nanostructures due to the multi-photon absorption effect. The results of this work show that the optical diffraction limit can be overcome by using a MLA with small lens diameter in combination with appropriate choice of laser power Lim et al 2006). …”
Section: Introductionmentioning
confidence: 86%
“…The periodicity of nanostructure array depends greatly on spacing between adjacent micro-lenses. 33,34 It had been shown that plasmonic nanolithography can reach down to 12 nm feature size. However, that techniques is limited to periodic structures.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The technique utilizes an array of focal points from a laser beam that also enables parallel patterning. 33,34 However, it requires micro-lens array fabrication prior to the fabrication of the intended nanostructures. The periodicity of nanostructure array depends greatly on spacing between adjacent micro-lenses.…”
Section: Discussionmentioning
confidence: 99%
“…The application of nanostructures could be largely enhanced once nanostructures are precisely characterized with a new method of fractal theory (as shown in Figure 1) [13][14][15]. Figure 1 The surface of different nano-sized dimensional structure characteristics on the same substrate Nowadays, most of nanodevices need to be made into a finished product to measure the specific surface area of them [16][17][18]. In this paper, we propose a method of measurement that the nanodevices can be measured by semi-finished products [19].…”
Section: Introductionmentioning
confidence: 99%